Issues of Organization of the Cardiac Surgical Care in Ukraine under Martial Law - Rudenko, Mykola L.; Unitska, Olha M.; Goriachev, Andrii G.; Andrushchenko, Tetiana A.; Verych, Nataliia M. (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To study and substantiate the new principles of organization in the provision of cardiac surgical care under martial law. Materials and methods. The article presents an analytical review using reference databases of scientific medical publications and analysis of our own database of cardiac surgical care for the period from 2014 to July 2023. The group of patients consisted of 501 male subjects. The age of the study participants varied from 21 to 58 years (mean age 41.5 ± 2.2 years). The analysis of monitoring results included the most common diseases of the circulatory system, combat injuries of the heart and main vessels. Results. The article pays attention to the current challenges that have arisen before organization of the system of providing cardiac surgical care under martial law. It is emphasized that the area of cardiac surgical assistance to military personnel is being developed at the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine since 2014, when the Anti-Terrorist Operation / Joint Forces Operation began. In cooperation with military doctors, new methods of treatment of patients with gunshot and mine-explosive wounds are being developed and implemented. It was established that among patients with cardiovascular pathology, combat injuries of the heart and main vessels make up 7.9%, which coincides with the frequency of combat injuries of the chest given in literary sources. Moreover, the length of hospital stay of patients with combat injuries of the heart and main vessels does not exceed the number of bed days during surgical treatment of the most common diseases of the circulatory system. It was also established that some of the injured patients had concomitant pathologies that required, in addition to cardiac surgical care, medical care of other specialists: a surgeon, a neurosurgeon, an orthopedic traumatologist, an otolaryngologist, a psychologist, etc. Conclusions. It has been established that organization of the system of providing cardiac surgical care under martial law is primarily designed to ensure: optimization of resources by strengthening the personnel reserve; cooperation with specialists of other specialties, medical institutions of various subordinates and international partners; changing patient routes taking into account, first of all, their safety; expanding narrow specialization of medical institutions by creating multidisciplinary teams.